Layered metal sulfides with MaSbc− framework (M = Sb, In, Sn) as ion exchangers for the removal of Cs(Ⅰ) and Sr(Ⅱ) from radioactive effluents: a review - Zhao, Qi; Wang, Shuai; Wu, Yichun; Wang, Yixuan; Ma, Shengshou; Shih, Kaimin (Frontiers in Chemistry, 2023)
Nuclear power has emerged as a pivotal contributor to the global electricity supply owing to its high efficiency and low-carbon characteristics. However, the rapid expansion of the nuclear industry has resulted in the production of a significant amount of hazardous effluents that contain various radionuclides, such as 137 Cs and 90 Sr. Effectively removing 137 Cs and 90 Sr from radioactive effluents prior to discharge is a critical challenge. Layered metal sulfides exhibit significant potential as ion exchangers for the efficient uptake of Cs + and Sr 2+ from aqueous solutions owing to their open and exchangeable frameworks and the distinctive properties of their soft S 2− ligands. This review provides a detailed account of layered metal sulfides with MaSb c− frameworks (M = Sb, In, Sn), including their synthesis methods, structural characteristics, and Cs + and Sr 2+ removal efficiencies. Furthermore, we highlight the advantages of layered metal sulfides, such as their relatively high ion exchange capacities, broad active pH ranges, and structural stability against acid and radiation, through a comparative evaluation with other conventional ion exchangers. Finally, we discuss the challenges regarding the practical application of layered metal sulfides in radionuclide scavenging.